Use of Computer Based Applications Across Fundional Areas of Management - Dharni, Khushdeep; Kiran, Ravi; Sharma, R K (Gyan Management Journal, 2008)
This paper aims to explore computer based information systems (CBIS) use in the firms acruss purpose dala ·oil Led fro11 :11 manufacl111 ing or 1anizalion · in Punjab. Results of Lh study ’un·Lional a1ea5, lnlu11 aliu,Jh:hnolugy rnanag 1